Possibilities of Systemic Anthropology from the Andes - Suárez Rojas, Luis Alberto (2021)
We propose to review the global as a complex, tense and dynamic system, configured both by new actors (banks, global corporations) and by institutional architectures, geographies of power and transnational networks. In short, we suggest a critical approach to globalization. In terms of hypotheses, we argue that a systemic anthropology is based on the logic of the world-system, taking Latin American thought and critical transformative theory into consideration. We assume that the global is neither abstract nor a tide that drags with local forms. The global is a concrete experience, from which multiple responses and frictions emerge.